Strategi Efektif Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Ibadah dan Pembentukan Karakter Religius Peserta Didik - Meliza Tri Afrilia; Ayu Trisnawati; Khatitan Khatitan; Resi Bela; Dedy Andryan (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
The purpose of this research is to identify and analyze the strategies implemented by Islamic Religious Education (PAI) teachers at Madrasah Aliyah to enhance the quality of worship and develop the religious character of students. This study aims to explore the methods and approaches used in PAI teaching, which not only cover cognitive aspects but also affective and spiritual dimensions, ensuring a deeper implementation of Islamic teachings in students' daily lives. Therefore, this research is expected to contribute to the development of effective teaching strategies to create students who not only understand Islamic teachings but also practice them well, and to serve as a reference for educators and policymakers in formulating relevant policies for fostering religious character in school environments.